Acute kinematic and kinetic adaptations to wearable resistance during vertical jumping. Issue 5 (28th May 2017) - Macadam, Paul; Simperingham, Kim D.; Cronin, John B.; Couture, Grace; Evison, Chloe
Abstract: One variation of vertical jump (VJ) training is resisted or weighted jump training, where wearable resistance (WR) enables jumping to be overloaded in a movement specific manner. A two-way analysis of variance with Bonferroni post hoc contrasts was used to determine the acute changes in VJ performance with differing load magnitudes and load placements. Kinematic and kinetic data were quantified using a force plate and contact mat. Twenty sport active subjects (age: 27.8 ± 3.8 years; body mass (BM): 70.2 ± 12.2 kg; height: 1.74 ± 0.78 m) volunteered to participate in the study. Subjects performed the counter movement jump (CMJ), drop jump (DJ) and pogo jump (PJ) wearing no resistance, 3% or 6% BM affixed to the upper or lower body. The main finding in terms of the landing phase was that the effect of WR was non-significant ( P  > .05) on peak ground reaction force. With regard to the propulsive phase the main findings were that for both the CMJ and DJ, WR resulted in a significant ( P   <  .05) decrease in jump height (CMJ: −12% to −17%, DJ: −10% to −14%); relative peak power (CMJ: −8% to −17%, DJ: −7% to −10%); and peak velocity (CMJ: −4% to −7%, DJ: −3% to −8%); while PJ reactive strength index was significantly reduced (−15% to −21%) with all WR conditions. Consideration should be given to the inclusion of WR in sports where VJ's are important components as it may provide a novel movement specific training stimulus. Highlights WR of 3 or 6 % BM provided a means to overload the subjects in this study resulting in decreased propulsive power and velocity that lead to a reduced jump height and landing force. Specific strength exercises that closely mimic sporting performance are more likely to optimise transference, therefore WR with light loads of 3–6% body mass (BM)appear a suitable tool for movement specific overload training and maximising transference to sporting performance. Practitioners can safely load their athletes with upper or lower body WR of 3–6% BM without fear of overloading the athletesover and above the landing forces they are typically accustomed too. As a training stimulus it would seem the WR loading provides adequate overload and athletes should focus on velocity of movement to improve power output and jump height i.e. take-off velocity.